WOMEN IDENTITY IN TAHMIMA ANAM’S THE BONES OF GRACE: STRUGGLE AGAINST PATRIARCHY - Fadriansyah, Naufal; Alfaris, Difa; rvn, Budyman (Jurnal Penelitian Humaniora, 2023)
The purpose of this study is to investigate identity struggle in the patriarchal cultures that exist in the novel The Bones of Grace. The qualitative technique was used in this study, and the results are presented using a descriptive model. The case study approach was used in this study. The major source for this study is Tahmima Anam's novel The Bones of Grace, which was published in 2016. This study uncovers Zubaida's struggle to challenge patriarchal society. The patriarchal cultures put Zubaida through an assigned identity that is restraining and controlling. However, this study discovered that through a new identity that Zubaida constructed herself, she can form a resistance to the patriarchal system that oppresses her.